Effect of morphology and simultaneous sulfation on Fe doped CeO2 for selective catalytic reduction of NOx with NH3. (15th February 2023) - Wang, Jinxiu; Liu, Yuqiu; Yi, Xianfang; Chen, Yanting; Yu, Yanke; Chen, Jinsheng
Graphical abstract: Highlights: Fe doped CeO2 catalysts present distinct shape dependent SCR catalytic activity. Sulfated Fe doped CeO2 porous nanorod catalyst performs excellent NO x conversion. Fe doping and sulfation induce porous nanorod shape with most exposed 1 1 0 faces. Surface sulfate species significantly increase Brønsted acid sites. SCR reaction mechanism is changed due to sulfation. Abstract: Researchers have been developing novel environment-friendly NH3 -SCR catalysts for controlling NO x emission from fossil fuel combustion. Fe doped CeO2 catalysts with nanorod, nanocube and nanopolyhedron shape were synthesized and sulfation was conducted on porous nanorod simultaneously. Their NO x conversions were in sequence of sulfated porous nanorod (S-FeCeO x ) > nanorod (R-FeCeO x ) > nanopolyhedron (P-FeCeO x ) > nanocube (C-FeCeO x ) and presented distinct morphology dependence. S-FeCeO x catalyst possessed above 95 % NO x conversion and nearly 100 % N2 selectivity in very high gas hourly space velocity of 240, 000 mL·g −1 ·h −1 at 275–400 °C. The sequence of BET specific surface area was: P-FeCeO x > R-FeCeO x > S-FeCeO x > C-FeCeO x and thus the change of physical adsorption capacity may be not the main reason for high SCR catalytic activity of S-FeCeO x and R-FeCeO x . Fe doping and sulfation induced porous nanorod shape with preferentially exposed 110 faces, most oxygen vacancy defect sites and highest surface chemisorbed oxygen ratio, which contributed to the highest NO x conversion of S-FeCeO x . Fe doping mainly increased strong acid sites, and surface sulfate species significantly increased Brønsted acid sites promoting NH3 adsorption and suppressed NO x adsorption on S-FeCeO x catalyst, beneficial to both high NO x conversion and low N2 O formation on it. R-FeCeO x catalyst mainly followed Langmuir-Hinshelwood mechanism, while SCR reaction mechanism was changed by sulfation and S-FeCeO x catalyst mainly followed Eley-Rideal mechanism.